Laser-induced anchoring of WO3 nanoparticles on reduced graphene oxide sheets for photocatalytic water decontamination and energy storage. Issue 1 (January 2020) - Ibrahim, Yusuf O.; Gondal, M.A.; Alaswad, A.; Moqbel, R.A.; Hassan, M.; Cevik, E.; Qahtan, T.F.; Dastageer, M.A.; Bozkurt, A.
Abstract: In this work, the synthesis of tungsten oxide/reduced graphene oxide (WO3 -rGO) nanocomposite, using a simple method of pulsed laser ablation in liquids (PLAL) is reported. The pulsed laser beam of 355 nm wavelength carries out two simultaneous processes: the reduction of graphene oxide and at the same time the anchoring of nanostructured WO3 on reduced graphene oxide. In the photo-catalytic application, WO3 -rGO shows much better visible light absorption and less photo-generated charge recombination than pure WO3, as indicated by optical absorption and photoluminescence spectra. These improved features in WO3 -rGO significantly enhanced the photo-catalytic decontamination of methylene blue (MB) dye in the water, compared to the use of pure WO3 as a photocatalyst. A Poly 2-acrylamido-2-methyl-1-propanesulfonic acid (PAMPS) based electrolyte together with the high electrical conductance and porosity of rGO which were produced after anchoring WO3 on the graphene oxide, were harnessed for the energy storage application using this material for a supercapacitor. The specific capacitance for WO3 -rGO based device is achieved to be 577 F g −1 measured by the galvanostatic charge-discharge (GCD) method. Also, at a power density of 1000 W kg −1, the as-synthesized WO3 -rGO demonstrated a large energy density value of 76.3 Wh Kg −1 that is much larger than obtained, using WO3 alone. Besides these photocatalytic and energy storage performance evaluation of WO3 -rGO, the optical, morphological and elemental characteristics of synthesized WO3 -rGO were also investigated to study the improved performance of the nanocomposite in these two applications.